Antithrombotic therapy in patients undergoing transcatheter aortic valve replacement: the complexity of the elderly. (6th November 2020) - Bencivenga, Leonardo; Sepe, Immacolata; Palaia, Maria Emiliana; Komici, Klara; Corbi, Graziamaria; Puzone, Brunella; Arcopinto, Michele; Cittadini, Antonio; Ferrara, Nicola; Femminella, Grazia Daniela; Rengo, Giuseppe
Abstract: Along with epidemiologic transitions of the global population, the burden of aortic stenosis (AS) is rapidly increasing and transcatheter aortic valve replacement (TAVR) has quickly spread; indeed, it is nowadays also employed in treating patients with AS at intermediate operative risk. Nonetheless, the less invasive interventional strategy still carries relevant issues concerning post-procedural optimal antithrombotic strategy, given the current indications provided by guidelines are not completely supported by evidence-based data. Geriatric patients suffer from high bleeding and thromboembolic risks, whose balance is particularly subtle due to the presence of concomitant conditions, such as atrial fibrillation and chronic kidney disease, that make the post-TAVR antithrombotic management particularly insidious. This scenario is further complicated by the lack of specific evidence regarding the 'real-life' complex conditions typical of the geriatric syndromes, thus, the management of such a heterogeneous population, ranging from healthy ageing to frailty, is far from being defined. The aim of the present review is to summarize the critical points and the most updated evidence regarding the post-TAVR antithrombotic approach in the geriatric population, with a specific focus on the most frequent clinical settings.